Exceptional Zeros and L-Invariants of Bianchi Modular Forms - Barrera-Salazar, D (American Mathematical Society, 2019)
Let f be a Bianchi modular form, that is, an automorphic form for GL2 over an imaginary quadratic field F. In this paper, we prove an exceptional zero conjecture in the case where f is new at a prime above p. More precisely, for each prime p of F above p we prove the existence of an L-invariant Lp, depending only on p and f, such that when the p-adic L-function of f has an exceptional zero at p, its derivative can be related to the classical L-value multiplied by Lp. The proof uses cohomological methods of Darmon and Orton, who proved similar results for GL2/Q. When p is not split and f is the base-change of a classical modular form f, werelateLp totheL-invariant of f, resolving a conjecture of Trifković in this case. © 2019 American Mathematical Society.